2012
DOI: 10.1007/s00253-012-4071-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the C-terminal antigenic domain of the malaria vaccine candidate Pfs48/45 in the green algae Chlamydomonas reinhardtii

Abstract: Malaria is a widespread and infectious disease that is a leading cause of death in many parts of the world. Eradication of malaria has been a major world health goal for decades, but one that still remains elusive. Other diseases have been eradicated using vaccination, but traditional vaccination methods have thus far been unsuccessful for malaria. Infection by Plasmodium species, the causative agent of malaria, is currently treated with drug-based therapies, but an increase in drug resistance has led to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Various TBV candidates have been successfully produced in plant system707172 with high recovery and desired immunogenicity (Table IV). Algae are also a promising system for the production of TBV that are orally delivered to avoid expensive purification and injectible delivery737475. These results sustain the feasibility of expressing TBV antigens in the plant based system.…”
Section: Production Of Tbvs In Plant Based Systemmentioning
confidence: 66%
See 1 more Smart Citation
“…Various TBV candidates have been successfully produced in plant system707172 with high recovery and desired immunogenicity (Table IV). Algae are also a promising system for the production of TBV that are orally delivered to avoid expensive purification and injectible delivery737475. These results sustain the feasibility of expressing TBV antigens in the plant based system.…”
Section: Production Of Tbvs In Plant Based Systemmentioning
confidence: 66%
“…Currently, many efforts for the development of transmission blocking malaria vaccine are focused on the production of TBV in plant-based expression system with a good safety profile, which are capable of inducing a strong immune response to reduce the malaria transmission717374. Completed clinical trials with Pfs25 formulations have been found immunogenic but shown some safety outcome issues like local and systemic adverse events8182.…”
Section: Discussionmentioning
confidence: 99%
“…A fully functional human IgG1 monoclonal antibody against anthrax protective antigen 83 was expressed from two separate genes and assembled into a fully active antibody (Tran et al, 2009). In addition, immunotoxins for cancer therapeutics as well as vaccine candidates against malaria or foot-and-mouth-disease virus have been produced in the chloroplast Jones et al, 2013). However, most of the recombinant proteins produced, have been soluble proteins, and furthermore have generally been proteins that can be considered 'benign' in that they have no effect on chloroplast metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…3 This surface protein plays a role in the male/female gamete interaction within the mosquito midgut. It is a member of a family of surface proteins that contain a 6-cysteine conserved domain structure and is believed to work in conjunction with a second member of this family of surface proteins, Pfs230, to allow for reproduction.…”
Section: Algae As a Malaria Vaccine Platformmentioning
confidence: 99%